Qualitative interview study of parents' perspectives, concerns and experiences of the management of lower respiratory tract infections in children in primary care. Issue 9 (15th September 2017) - Halls, Amy; van't Hoff, Catherine; Little, Paul; Verheij, Theo; Leydon, Geraldine M
Abstract : Objective: To explore parents' perspectives, concerns and experiences of the management of lower respiratory tract infections (LRTIs) in children in primary care. Design: Qualitative semistructured interview study. Setting: UK primary care. Participants: 23 parents of children aged 6 months to 10 years presenting with LRTI in primary care. Method: Thematic analysis of semistructured interviews (either in person or by telephone) conducted with parents to explore their experiences and views on their children being prescribed antibiotics for LRTI. Results: Four major themes were identified and these are perspectives on: (1) infection, (2) antibiotic use, (3) the general practitioner (GP) appointment and (4) decision making around prescribing. Symptomatic relief was a key concern: the most troublesome symptoms were cough, breathing difficulty, fever and malaise. Many parents were reluctant to use self-care medication, tended to support antibiotic use and believed they are effective for symptoms, illness duration and for preventing complications. However, parental expectations varied from a desire for reassurance and advice to an explicit preference for an antibiotic prescription. These preferences were shaped by: (1) the age of the child, with younger children perceived as more vulnerable because of their greater difficulty in communicating, and concerns about rapid deterioration; (2) the perceived severity of the illness; and (3) disruption to daily routine. When there was disagreement with the GP, parents described feeling dismissed, and they were critical of inconsistent prescribing when they reconsult. When agreement between the parent and the doctor featured, parents described a feeling of relief and legitimation for consulting, feeling reassured that the illness did indeed warrant a doctor's attention. Conclusion: Symptomatic relief is a major concern for parents. Careful exploration of expectations, and eliciting worries about key symptoms and impact on daily life will be needed to help parents understand when a no antibiotic recommendation or delayed antibiotic recommendation is made.